(x, y) = (
,
)
given the 2 equations
5x - 3y - 10 = 0 → (1)
x + y - 7 = 0 → (2)
rearrange (2) to obtain y in terms of x
y = 7 - x → (3)
Substitute y = 7 - x into (1)
5x - 3(7 - x) - 10 = 0
5x - 21 + 3x - 10 = 0
8x - 31 = 0 ( add 31 to both sides )
8x = 31 ( divide both sides by 8 )
x =
![(31)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xqixo1px1rfd2yy1ugerwcen70jw76ubib.png)
Substitute this value into (3) for y
y = 7 - x =
-
=
![(25)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8v8jhiz11ce77qal381qc3m33osvkivonj.png)